Clinical efficacy of electrosurgery and steel scalpel surgery for umbilical herniorrhaphy in bovine calves: A comparative analysis - Mohammad Raguib Munif; Md Ariful Islam; Md Sabuj Rahman; Md Mizanur Rahman; Md Rafiqul Alam (Heliyon)
Electrosurgery (ES) offers a promising alternative to conventional steel scalpel surgery (SSS), providing superior hemorrhage control and efficient tissue dissection with minimal invasiveness. Given the limited literature, this study aims to compare the clinical efficacy of ES with that of SSS in bovine umbilical herniorrhaphy. Fourteen crossbred male calves with reducible umbilical hernias, aged less than one month and weighing 25–47 kg, were randomly assigned to two experimental groups: group A (ES) and group B (SSS), each containing seven calves. Clinical parameters, such as temperature, heart rate, respiratory rate, and SpO2, were recorded 10 min preoperatively, intraoperatively at 20 and 40 min, and 10 min postoperatively. Hematobiochemical parameters, including total erythrocyte count, hemoglobin, packed cell volume, total serum protein, blood urea nitrogen, and creatinine, were also assessed at these intervals. Skin incision length, volume of blood loss, surgical duration, healing time, postoperative complications, and postoperative pain response were documented. Furthermore, a sonographic evaluation of postoperative wound healing was conducted. The clinical and hematobiochemical parameters did not vary significantly between the groups. However, significant variations (p<0.05) were noted in skin incision length, volume of blood loss, surgical duration, and healing time between the groups. Group A calves experienced smaller incisions, reduced blood loss, shorter surgical duration, quicker recovery, and fewer postoperative complications and pain. The ultrasonographic evaluation revealed superior postoperative wound healing in group A compared to group B. These findings suggest that ES is a more effective clinical approach than traditional SSS for umbilical herniorrhaphy in bovine calves.